TAAR1 in Addiction: Looking Beyond the Tip of the Iceberg - Liu, Jian-Feng; Li, Jun-Xu (Frontiers in Pharmacology, 2018)
Trace-amine associated receptor 1 (TAAR1) is the best-characterized member of the family of TAARs. TAAR1 is broadly expressed in the brain, especially within the monoaminergic systems. Evidence from electrophysiological and neurochemical studies evaluating the effects of genetic and pharmacological interventions on TAAR1 revealed that TAAR1 modulates transmission of monoamines, especially dopamine. TAAR1 agonists dampened drugs of abuse-induced dopamine accumulation. In general, TAAR1 agonists specifically inhibited the rewarding and reinforcing effects of drugs of abuse and drug-abuse related behaviors. Details of the mechanism of TAAR1 remain elusive; however, it is thought to be regulated by its interactions with D2 receptors. In addition, the alternative cellular mechanism such as an interaction between TAAR1 and D3 may also participate in the action of TAAR1 agonists. Further studies are required to investigate the role of TAAR1 in other drugs of abuse-related behaviors and the underlying neural mechanisms. Collectively, TAAR1 negatively modulates dopaminergic systems and dopamine-related behaviors and TAAR1 agonists are promising pharmacotherapy to treat drug addiction and relapse.